WRITERâ€™S WAYS TO INTERACT WITH READERS IN THE TEXTS WRITTEN BY THE STUDENTS OF ENGLISH EDUCATION DEPARTMENT IN MURIA KUDUS UNIVERSITY - Perwikasih Utari, Aisyah Ririn (Vision: Journal for Language and Foreign Language Learning, 2016)
Written text is more complex than spoken text. The interac- tion between the sender and the receiver are not intensively reached. Readers can only give response without being known by the writer. This is why the writer should write the text in some consideration of leading the readers to read further or even give comments. This research is a qualitative research, which aims to ï¬nd out the writerâ€™s way to interact with readers in four components: 1) clause structure, 2) terms of address, 3) modality, 4) evaluating phenomena. The data of the research is the writerâ€™s way of interacting with readers and the source is the texts written by the students of English Education Department in Muria Kudus University. The result of the research covers that most of the writers use statements and questions as the clause structure. The terms of address used are â€œweâ€, â€œyouâ€, and â€œIâ€. The modality which is mostly used is medium degree such as â€œcanâ€. The evaluating phenomena are about the sharing of life ex- perience. There are some other ways ofÂ  writerâ€™s interaction with readers through texts that can be conducted in the next research.